Politikai modernizáció az Oszmán Birodalomban : 1774-1914 - Majoros, István (Közép-Európai Közlemények, 2013)
The study presents a process of political modernisation of European type in the Ottoman Empire from the peace treaty of Küçük-Kaynarca to the First World War. The culmination of this process was the proclamation of the constitution in 1876. But this constitution didn’t work to the Young Turkish Revolution in 1908. The study presents the situation of the empire, the causes of the reforms, first of all the Tanzimat and the the policy of the sultans from Abdul-Hamid I to Abdul-Hamid II. The author examines changes under Abdul-Hamid II and he tries to explain the causes of his new policy. At the end he comes to the conclusion that the presented political modernisation in spite of the contradictions was a good basis to be continued in the interwar period and after the Second World War.